Social Work Students in the Aftermath of the Great Flood of 2016: Mental Health, Substance Use, and Adaptive Coping. (1st October 2020) - Lemieux, Catherine M.; Moles, Aimee; Brown, Kimberly M.; Borskey, Erma J.
ABSTRACT: The postdisaster experiences of social work students have been the focus of a growing corpus of research in the past two decades; however, few investigations have been conducted in the context of catastrophic flooding events. The present study examined coping responses and mental health among 186 social work students in the aftermath of the Great Flood of 2016. The majority showed clinical levels of depression, at 59.1%, with 16.3% reporting substance use as coping and 3.6% scoring at or above the clinical level for posttraumatic stress symptoms. Well over half of the students (54.3%) employed 6 or more of 10 adaptive coping strategies. Students' negative emotions, negative reactions, and flood-related stressors correlated with all 10 of the adaptive coping responses. Negative reactions were associated with symptomology and coping via substance use. African- American students showed higher scores than their European-American counterparts on all measures of adaptive coping, protective factors, mental health symptomology, and substance use as coping. There is a need to inform faculty, field staff, and supervisors about the potential risks when distressed students provide postdisaster services to traumatized populations. Culturally responsive and trauma-informed supervision approaches are recommended to cultivate students' resilience and prevent distress and secondary traumatization.